Cytoplasmic strings between ICM and mTE are a positive predictor of clinical pregnancy and live birth outcomes: A time-lapse study - Ma, Bing-Xin; Yang, Liu; Tian, Yu; Jin, Lei; Huang, Bo (Frontiers in Medicine, 2022)
Background: Elective single blastocyst transfer (eSBT) is considered to reduce the incidence of multiple pregnancy compared to double embryo transfer. Blastocyst selection is the key to achieving pregnancy. In the past, morphological assessment was the main criterion used to select blastocyst. Some important morphological parameters are considered to be clinically valuable, such as cytoplasmic strings traversing from the inner cell mass (ICM) and mural trophectoderm (mTE). Methods: In this study, 1,267 elective frozen-thawed eSBT cycles cultured in a time-lapse culture system from January 2018 to May 2019 were included. Blastocysts were grouped into “present” and “absent” according to the appearance of cytoplasmic strings between ICM and mTE cells. The “present” group was further categorized according to the quantity of cytoplasmic strings between the ICM and mTE cells. Results: A time-lapse analysis indicated that cytoplasmic strings between ICM and mTE were more visible among good quality blastocysts. Furthermore, blastocysts with cytoplasmic strings showed higher clinical pregnancy and live birth rates (P=0.011 and 0.003), while no significant differences were observed in abortion rate and birth weight (P=0.466 and 0.556). Conclusions: In conclusion, although the results of previous studies about cytoplasmic strings have been controversial, the present time-lapse analysis provides evidence for the first time that cytoplasmic strings between ICM and mTE cells are a positive predictor of clinical pregnancy and live birth outcomes in elective frozen-thawed single blastocyst transfer cycles.